Influence of Regional Financial Independence and Audit Opinion on Corruption Levels in Local Governments - Kartika Putri Hutabarat; Juniati Gunawan; Corina ak Joseph (International Journal of Business and Quality Research, 2024)
The numerous disclosures of corruption cases involving local government officials and members of the local legislature indicate that corruption is severe at the regional level. The study aims to examine the influence of regional financial independence and audit opinions on the corruption level in the local government in Indonesia. Using secondary data from the Regional Government Financial Report, Summary of Examination Results by Audit Board of Indonesia, and the ruling in kracht of the Supreme Court, the study involved 542 regional governments for the period of 2022. The analytical method used is double linear regression using SPSS software version 26. The results of the research show that the regional financial independence has a significant negative influence on the level of corruption, while the audit opinions have no significant influence. The size of the local government has also been found to have a significant positive influence on the level of corruption. This research provides important insights into the efforts to prevent corruption at the local government level.